2013
DOI: 10.1002/jor.22375
|View full text |Cite
|
Sign up to set email alerts
|

Functional testing provides unique insights into the pathomechanics of femoroacetabular impingement and an objective basis for evaluating treatment outcome

Abstract: Femoroacetabular impingement (FAI) has been recognized as a significant clinical problem. While hip reshaping surgery for treating FAI has had positive clinical outcomes, there remains a need for objective functional outcomes of FAI treatment. We tested the hypothesis that during walking and stair climbing significant changes in hip kinematics would occur following hip reshaping surgery that indicate restoration of normal function post-operatively. Hip and pelvic kinematics were collected for 17 FAI patients p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 40 publications
(50 reference statements)
7
117
3
Order By: Relevance
“…M a n u s c r i p t Five studies have compared gait biomechanics between people with and without symptomatic FAI. Our observed 4°reduction in sagittal plane ROM in those with symptomatic FAI is consistent with two previous studies that also reported deficits in sagittal plane motion of 4° [ 13,19]. Although statistically different from the disorder-free participants, the clinical significance of this hip ROM impairment is unknown.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…M a n u s c r i p t Five studies have compared gait biomechanics between people with and without symptomatic FAI. Our observed 4°reduction in sagittal plane ROM in those with symptomatic FAI is consistent with two previous studies that also reported deficits in sagittal plane motion of 4° [ 13,19]. Although statistically different from the disorder-free participants, the clinical significance of this hip ROM impairment is unknown.…”
Section: Resultssupporting
confidence: 90%
“…Gait is the most common repetitive voluntary movement of the lower limbs and an essential activity of daily living. There is limited and conflicting evidence regarding alterations to hip ROM during gait in individuals with symptomatic FAI [13,[17][18][19][20]. Interpretation of current evidence is limited by the use of narrow patient samples that render it difficult to generalize results to the broader FAI population, and the failure to use diagnostic imaging to ensure healthy controls in the comparison groups have no evidence of asymptomatic morphological FAI.…”
Section: Introductionmentioning
confidence: 99%
“…While hip abductor muscle weakness is common to GT (Allison et al, 2016a;Woodley et al, 2008), hip OA (Loureiro et al, 2013) and FAI (Casartelli et al, 2011), its relationship with kinematics of stair ascent may differ. No frontal plane differences in stair kinematics have been identified between individuals with and without FAI, but this analysis excluded evaluation of the trunk (Rylander et al, 2013). Conversely, a recent study by Meyer et al(2015) of individuals with mostly advanced hip OA (mean age 49.9 years) identified lower HADM and greater ipsilateral trunk lean during stair ascent (step height -184 mm).…”
Section: Accepted M Manuscriptmentioning
confidence: 92%
“…Although stair ascent has not been studied in participants with GT, previous studies have included individuals with intra-articular hip pathology, including hip OA (Meyer et al, 2015), femoroacetabular impingement (FAI) (Rylander et al, 2013). While hip abductor muscle weakness is common to GT (Allison et al, 2016a;Woodley et al, 2008), hip OA (Loureiro et al, 2013) and FAI (Casartelli et al, 2011), its relationship with kinematics of stair ascent may differ.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Many studies have attempted to better understand how sometimes subtle morphologic differences can lead to the eventual painful injury associated with FAI, but each is with their weaknesses. Motion-capture methods have been utilized to understand the dynamic presentation of FAI during common activities of daily living, and to assess surgical treatment of the condition quantitatively [5,8]. However, motion-capture alone cannot directly visualize the interactions of the internal structures.…”
mentioning
confidence: 99%